POLYAMINES AS SALINITY BIOCHEMICAL MARKER IN CALLUS OF Eucalyptus urograndis - Lima, Giuseppina Pace Pereira [UNESP]; Piza, Isabela M. Toledo [UNESP]; Henrique, Andréa; Takaki, Massanori [UNESP] (Universidade Federal de Santa Maria, 2003)
Biochemical markers have been used for the analysis of plant cells submitted to several types of stress, among them salinity. This work aimed at analyzing the effect of saline stress in callus of Eucalyptus urograndis on polyamine contents. Explants (hypocotyls) obtained from seeds were inoculated in callus inductive medium, submitted to different levels of NaCl and analyzed at 10, 20 and 30 days after the inoculation. The free polyamines were extracted, isolated and quantified using TLC (Thin-Layer Chromatography). Putrescine content was higher and a fall in the spermidine content was observed in callus submitted to salinity condition. The results showed that polyamine accumulation is related to NaCl exposure in callus of Eucalyptus urograndis. The decrease in spermine content could be used as a biochemical marker for Eucalyptus callus subjected to salinity.

Marcadores bioquímicos têm sido usados na análise de plantas submetidas a vários tipos de estresse, entre eles a salinidade. Este trabalho teve como objetivo analisar o estresse salino em calos de Eucalyptus urograndis em relação ao conteúdo de poliaminas. Explantes (hipocótilos) obtidos de sementes foram inoculados em meio indutivo de calos e foram submetidos a diferentes níveis de NaCl e analisados aos 10, 20 e 30 dias de inoculação. As poliaminas livres foram extraídas, isoladas e quantificadas usando TLC (Cromatografia de Camada Delgada). O conteúdo de putrescina foi maior, enquanto que o conteúdo de espermidina apresentou decréscimo, em calos submetidos a condições salinas. Os resultados mostram que o acúmulo de putrescina está relacionado com a exposição a NaCl em calos de Eucalyptus urograndis. A diminuição do conteúdo de espermina pode ser usada como marcador bioquímico de calos de Eucalyptus sujeitos à salinidade.
POLIAMINAS COMO MARCADORES BIOQUÍMICOS DE SALINIDADE EM CALOS DE Eucalyptus urograndis
Keywords: micropropagation; salt stress; polyamines; Eucalyptus.; micropropagação; estresse salino; poliaminas; Eucalyptus